Hutchinson Pocket Dictionary of Classical Music - Publishing, Helicon (Helicon Publishing, 2005)
Quick and easy reference to classical music.
Keywords: Electronic books. -- local; Encyclopedias and dictionaries; Music -- Dictionaries